Electronic delocalization, charge transfer and hypochromism in the UV absorption spectrum of polyadenine unravelled by multiscale computations and quantitative wavefunction analysis. Issue 8 (21st June 2017) - Nogueira, Juan J.; Plasser, Felix; González, Leticia
Abstract : We show that in polyadenine UV photons are absorbed by excitons localized on up to three adjacent nucleobases. Abstract : The characterization of the electronically excited states of DNA strands populated upon solar UV light absorption is essential to unveil light-induced DNA damage and repair processes. We report a comprehensive analysis of the electronic properties of the UV spectrum of single-stranded polyadenine based on theoretical calculations that include excitations over eight nucleobases of the DNA strand and environmental effects by a multiscale quantum mechanics/molecular mechanics scheme, conformational sampling by molecular dynamics, and a meaningful interpretation of the electronic structure by quantitative wavefunction analysis. We show that electronic excitations are extended mainly over two nucleobases with additional important contributions of monomer-like excitations and excitons delocalized over three monomers. Half of the spectral intensity derives from locally excited and Frenkel exciton states, while states with partial charge-transfer character account for the other half and pure charge-transfer states represent only a minor contribution. The hypochromism observed when going from the isolated monomer to the strand occurs independently from delocalization and charge transfer and is instead explained by long-range environmental perturbations of the monomer states.